Boosting piezoelectric response of PVDF-TrFE via MXene for self-powered linear pressure sensor - Wang, Shan; Shao, He-Qing; Liu, Yong; Tang, Chun-Yan; Zhao, Xing; Ke, Kai; Bao, Rui-Ying; Yang, Ming-Bo; Yang, Wei (Composites science and technology, 2021)
Piezoelectric film pressure sensors are forthcoming choices for self-powered flexible and portable electronics because of their unique advantages in instant response and linear pressure-electrical signal relationship. However, it is commonly of challenge to achieve high output voltage response to pressure in piezoelectric polymer films. Here, we report a piezoelectric film pressure sensor fabricated by electrospun polyvinylidene-fluoride-trifluoroethylene (PVDF-TrFE)/MXene nanofiber mats. As a new two-dimensional nanomaterial, MXene has not only a large amount of surface functional groups to enable interaction with the dipoles of PVDF-TrFE molecular chains, but also high electrical conductivity to potentially increase the polarization of PVDF-TrFE during electrospinning. As such, by comparison with the control pressure sensor consisting of neat PVDF-TrFE film, the composite film sensor shows significantly improved output voltage, and the improvements are closely dependent on MXene content. For instance, the composite film with 2.0 wt% MXene can achieve an instantaneous output power density of ~3.64 mW/m2 under the pressure of 20 N with the frequency of 1 Hz. Such piezoelectric PVDF-TrFE/MXene films are capable of sensing body motion for healthcare. Furthermore, the hydrophilicity of MXene allows the film pressure sensor to monitor humidity change, thus the composite film sensor demonstrates potential application in multifunctional electronic skins. The electrospun PVDF-TrFE/MXene composite film with good piezoelectric properties shows a good linear pressure-electrical signal response and ability of sensing human daily activities. [Display omitted]